Political stability and public governance in Peru - Heredia Llatas, Flor Delicia (2023)
The political polarization between the executive and legislative powers precipitated a crisis in the political institutions, affecting the politicalStability of the rulers and the management of administrative systems; however, under governance in public administration, the link it generates between governance and democracy must be clarified. The objective was to determine the connection between politicalStability and public administration in Peru. The employed methodology is of the applied variety, with a quantitative approach, under the positivist paradigm and a non-experimental transversal correlational design. The World Bank Indicators (WDI) were used to compile the secondary data from 1986 to 2021. The dynamic Autoregressive distributed lag (ARDL) method examinedthe relationship between the variables. The results indicate that politicalstability positively affectsPeru's public administration. Politicalstability bolsters institutionalization, enables governability, and enhances governance by providing continuity to public, state, and government policies that promote national development.